Utilization of antigen-specific host responses in the evaluation of Mycobacterium tuberculosis infection, development of disease and treatment effect - Menezes, Angela Maria (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)--Stellenbosch University, 2013.